Critical Analysis of Advanced Nursing Roles, Practice Guidelines, and Patient-Centered Care - Abotaleb, Fatema Hussin; Alshehri, Alanood Faraj; Alyami, Tahane Marzooq; Alhadad, Noof Ali; Saad, Munirah Jmaan; Albelharth, Zakia Hajjas; Al Makhals, Abeer Hamed; Al najey, Layla Hassan; Al-Najrani, Hamdah Khaled Saeed; Asiri, Khatmah Mohammed Ali (Journal of Ecohumanism, 2024)
This paper presents a comprehensive evaluation of such issues as the advanced nursing roles, the guidelines of the practice, and patient-centred care in modern healthcare facilities. The changes in APN roles of NPs, CNSs, CRNAs, and CNMs in light of patient benefits, quality of care, and other issues in healthcare are variously reviewed. Practice guidelines outlining a specific structure for APN roles and responsibilities are also discussed. Moreover, practical implications of patient-centred care, PCCT, are discussed to ascertain how they can help enhance communication and care providers’ patient partnerships in healthcare delivery, especially when it comes to providing home-centred rather than disease-centred, advanced, individualized care. This paper combines findings from the literature and research theories and provides a substantial analysis of the continuous change process in the area of nursing.